A Behaviour of Religious Moderation among Salafi in Ambon - Sugi, La; Rahman, Muhajir Abd.; Kamarzaman, Mohd Haidhar (Balai Penelitian dan Pengembangan Agama Semarang, 2023)
Salafi community in Ambon have developed since the arrival of Laskar Jihad during the 1999 Ambon Conflict. Social dan religious competition has divided them, which is not only triggered by their interpretation of Islam but also by their efforts to gain religious influence and socio-religious dominance within the Islamic society. The research method used in this research is qualitative phenomenology. The research results found that for the Salafis, love for their homeland was proven during the COVID-19 pandemic; Salafi groups in Ambon also implement all policies issued by the Indonesian government without exception. Religious moderation is a fair and balanced attitude that does not exaggerate or belittle religion. Another characteristic of the moderation attitude shown is constantly repairing and avoiding damage. Salafi community in Ambon continue try to protect their faith, soul, reason, honor, lineage, and property. They respect fellow religious people, regardless their religious background and beliefs.